Responding with care: A careful critical approach within educational health promotion - Gunnarsson, Karin (Reconceptualizing Educational Research Methodology, 2018)
By engaging with a manual based program called DISA this paper explores how care is enacted in educational health promotion and moreover elaborates on how to engage methodologically with a careful critique. Together with sociomaterialist scholars I propose a theoretical and methodological notion of care that includes the vital doings of materialities, discourses and affectivity. Working with this notion of care makes it possible to engage with exclusions and power while at the same time open up for the erratic and unpredictable. To do this I put to work the concepts translation and touch. With these concepts it becomes possible to acknowledge the transformations taking place within the practice and avoid becoming stuck in stabilization and negativity. Not to ignore the orderings of the practice but to work actively through negativity into a generative potential. This shows that how to respond with care cannot be determined by ready-made instructions. It involves creating an imaginative and fluid practice since care always becomes a moving and temporary matter.